A Prospective Safety Study of Autologous Adipose-Derived Stromal Vascular Fraction Using a Specialized Surgical Processing System. Issue 3 (September 2017) - Berman, Mark; Lander, Elliot
Autologous adipose-derived stromal vascular fraction (SVF) has been proposed as a remedy for a number of inflammatory, autoimmune, and degenerative conditions. This procedure had mainly been evaluated in veterinary medicine and outside the United States when this study was initiated. This study looks at adverse events to evaluate safety as its primary objective and secondarily follows efficacy of SVF as deployed through intra-articular injections and intravenous infusions for a variety of orthopedic and non-orthopedic conditions. We hypothesized that autologous SVF deployment using a specialized surgical processing system (the CSN Time Machine® system, trademark name for the MediKhan Lipokit/Maxstem system; MediKhan, Los Angeles, California) was safe (ie, minimally acceptable adverse events) and that clinical efficacy could be demonstrated. This was a prospective case series. After institutional review board approval, 1698 SVF deployment procedures were performed between 2011 and 2016 by us and other affiliates with our same system trained by us as a nearly closed sterile surgical lipotransfer procedure on 1524 patients with various degenerative, inflammatory, and autoimmune conditions with a majority involving the musculoskeletal system. All outcome test data were collected in an online database over a 5-year period. Our study shows a very low number of reported adverse events and a reduction in pain ratings after 6 months or more across a variety of musculoskeletal diseases and improvements in a variety of other degenerative conditions. Our system for producing adipose-derived SVF therapy for our patients was safe and benefits could be measured for a long time after SVF deployment. Further controlled long-term studies for specific disease conditions with large patient populations are necessary to further investigate the benefits observed.